Spin Crossover in a Cobalt Complex on Ag(111). (2nd February 2022) - Johannsen, Sven; Ossinger, Sascha; Grunwald, Jan; Herman, Alexander; Wende, Heiko; Tuczek, Felix; Gruber, Manuel; Berndt, Richard
Abstract: The Co‐based complex [Co(H2 B(pz)(pypz))2 ] (py=pyridine, pz=pyrazole) deposited on Ag(111) was investigated with scanning tunneling microscopy at ≈5 K. Due to a bis(tridentate) coordination sphere the molecules aggregate mainly into tetramers. Individual complexes in these tetramers undergo reversible transitions between two states with characteristic image contrasts when current is passed through them or one of their neighbors. Two molecules exhibit this bistability while the other two molecules are stable. The transition rates vary linearly with the tunneling current and exhibit an intriguing dependence on the bias voltage and its polarity. We interpret the states as being due to S = 1 / 2 and 3 / 2 spin states of the Co 2+ complex. The image contrast and the orders‐of‐magnitude variations of the switching yields can be tentatively understood from the calculated orbital structures of the two spin states, thus providing first insights into the mechanism of electron‐induced excited spin‐state trapping (ELIESST). Abstract : Spin‐crossover is induced in self‐assembled tetramers of a Co‐complex on Ag(111) surfaces via the injection of electrons or holes with a scanning tunneling microscope. The resulting memristive current–voltage characteristic is analysed in terms of the electron transport through the molecular d‐orbitals.